Characterization of Polyphenols and Volatile Compounds from Understudied Algerian Pallenis spinosa by HS-SPME-GC-MS, NMR and HPLC-MSn Approaches - Nabila Adoui; Nabila Souilah; Hamdi Bendif; Stefania Sut; Stefano Dall’Acqua; Guido Flamini; Filippo Maggi; Gregorio Peron (Applied Sciences, 2023)
Pallenis spinosa (L.) Cass. is a widespread plant in the Mediterranean region. Traditionally, it is used as a medicinal species to treat several ailments, from inflammation to skin injuries. Although the phytochemical content of this plant has already been investigated, there is currently limited data on Algerian P. spinosa. In this work, we focused on volatile compounds and non-volatile secondary metabolites extracted using HS-SPME and methanol from the aerial parts of P. spinosa collected from Northeast Algeria. Volatile constituents were analyzed by GC-MS, while non-volatile compounds were analyzed by NMR and HPLC-MSn. In total, 48 volatile compounds were identified, including sesquiterpene hydrocarbons (65.8%), monoterpene hydrocarbons (16.9%), and oxygenated monoterpenes and sesquiterpenes (8.3% and 6.5%, respectively). β-Chamigrene (16.2%), α-selinene (12.8%), β-pinene (10.6%), and β-caryophyllene (9.2%) were assessed as the main constituents. Concerning non-volatile metabolites, 23 polyphenols were identified (7.26 mg/g DW), and phenolic acids were predominant (5.83 mg/g DW). Tricaffeoylhexaric acid (1.76 mg/g DW), tetracaffeoylhexaric acid (1.41 mg/g DW), 3,5-dicaffeoylquinic acid (1.04 mg/g DW), caffeoyl dihexoside (0.35 mg/g DW), and chlorogenic acid (0.29 mg/g DW) were the most abundant ones. Several known flavonoids, such as tricin and patuletin glycosides, kaempferol, and apigenin, were also identified, and myricetin hexoside was detected in P. spinosa for the first time. Overall, our work is the first to report an exhaustive characterization of volatile and non-volatile secondary metabolites from Algerian P. spinosa. The results represent a step forward in revealing the chemistry of this widespread plant species. Furthermore, they may contribute to rationalizing its traditional medicinal applications and preserve the biodiversity of Algerian flora.